2012
DOI: 10.1134/s1063773712010021
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity of the neutron star crust at low temperatures

Abstract: Abstract-The electrical conductivity of the neutron star crust at low temperatures is calculated by taking into account the mixing of the electron wave functions due to the interaction with the crystal lattice of atomic nuclei. We show that the previously existed model of exponential reduction of the electron-ion scattering rate can lead to an overestimation of the electrical conductivity by several orders of magnitude. We propose a simple interpolation formula for use in applications that joins the previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
2
18
0
1
Order By: Relevance
“…This implied that at T < T U the conductivity would be in practice determined by impurities and structure defects of the lattice, rather than by the electron-phonon scattering . However, Chugunov (2012) showed that distortion of electron wave functions due to interaction with the Coulomb lattice destroys this picture and strongly slows down the increase of the conductivity. As a result, the conductivities in neutron star envelopes can be treated neglecting the "freezing-out" of the Umklapp processes.…”
Section: A21 Electron-ion Scatteringmentioning
confidence: 99%
“…This implied that at T < T U the conductivity would be in practice determined by impurities and structure defects of the lattice, rather than by the electron-phonon scattering . However, Chugunov (2012) showed that distortion of electron wave functions due to interaction with the Coulomb lattice destroys this picture and strongly slows down the increase of the conductivity. As a result, the conductivities in neutron star envelopes can be treated neglecting the "freezing-out" of the Umklapp processes.…”
Section: A21 Electron-ion Scatteringmentioning
confidence: 99%
“…While these assumptions make the numerical computation feasible, further processes may affect the formation of magnetic spots. In principle, the magnetic field evolution is coupled to its thermal evolution, as conductivity is a function of temperature (Chugunov 2012). Moreover, thermoelectric effects can in principle increase the magnetic field and consequently enhance its strength in regions where high temperature gradients appear (Urpin & Yakovlev 1980;Geppert 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We used a numerical model that incorporates state-of-the-art microphysics involving the electrical conductivity at the neutron star crust (Potekhin 1999;Chugunov 2012) and consistent thermal evolution profiles (Aguilera et al 2008). Our treatment took into account diffusion of the currents in the neutron star crust and advection of the field as a direct consequence of the matter accretion onto the surface.…”
Section: Discussionmentioning
confidence: 99%
“…In the NS crust, the principal charge carriers are the electrons, and thus the transport coefficient, σ, is determined taking into account every electron scattering-on processes: ions (p), phonons (ph), and impurities (Q). We used the non-quantizing electron conductivity from a public code 1 based on Potekhin (1999), with the modifications introduced by Chugunov (2012). These routines give σ as a function of the temperature, T , density, ρ, magnetic field, B, atomic and mass numbers, (Z, A), auxiliary mass number, which incorporates the free neutron gas, A * , and the impurity content parameter, Q = Z 2 imp .…”
Section: Magnetic Field Evolutionmentioning
confidence: 99%